Efficiency the Training (CoRT) Program –Section One- to Develop the Critical Thinking A Semi -Empirical Study of the Sixth Primary Pupils in Lattakia- - - Jdeed, Lubna; Mobayed , Mouhannad; Abbas, Rana (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This research aimes to determine efficiency the training CoRT program –section one- to developing critical thinking, and the study sample consisted of (95) male and female pupils from the sixth primary classroom, including (48) males and (47) females, who were dividual randomly to two groups: experimental group and control group. And to achieve the objectives of the current research, we used training CoRT program –section one- designed by (DeBono, 1970) and the Langrehr critical thinking test (Langrehr, 2000) this research followed semi- empirical methodology, and data were processed using (SPSS) program. The research reached several results, the most important of which are: - the efficiency of training CoRT program –section one- on developing critical thinking of the sixth primary pupils in Lattakia, Eta square was (0.716), in favor of the experimental group. - there was no significant difference between males and females pupils from experimental group on the test of critical thinking. The research end into several recommendations, the most important was: including our curriculums programs, relating daily life and its several stands, away of academic articles, to develop the critical thinking, such as training CoRT program.